Pathways of Escherichia coli transfer from animal manure: risks and mitigation in agriculture - Nunzio Sarnino; Subhasish Basak; Lucie Collineau; Roswitha Merle (Frontiers in Public Health)
Animal manure is applied in agriculture to improve soil fertility and crop yield. Nonetheless, manure can also carry Escherichia coli (E. coli), including antibiotic-resistant strains. Therefore, it may pose a risk for environmental contamination. This review includes 50 studies which were identified from the search terms related to the transmission of E. coli through manure. The review outlines the potential routes of E. coli transmission from manure to soil, water and crops and which factors most critically determine persistence and contamination. The persistence of E. coli in soil is highly variable, ranging from <30 days for composted manures to more than 200 days in cooler conditions. These differences depend on the type of manure used, the environmental conditions and the treatment employed. While crops can be contaminated directly through application of manure, contaminated irrigation water may be a more important pathway. The foremost cause of surface water contamination seems to be rainfall runoff, whereas groundwater contamination is rather uncommon, mainly happening in areas with specific soil conditions. Composting and adherence to pre-harvest intervals are very effective mitigation strategies that can greatly reduce contamination risks. Overall, this review identifies research gaps on water contamination pathways and the persistence of resistant strains. Moreover, it sets up the basis for the development of robust risk assessments and evidence-informed approaches to address the contamination risks that are linked to animal manure.